Hereditary deficiency of OKT4-positive cells: studies for mode of inheritance and lymphocyte functions. - Fukuda, T (1984)
Two Graves' patients were found to have no OKT4+ cells in their peripheral blood lymphocytes (PBL). However, the reactivity of their lymphocytes with T4(T4A) and anti Leu-3a was normal and no autoantibodies to the OKT4 determinant were found in their sera. Cytofluorographic analysis of PBL from their family members showed three types of immunofluorescence profiles with OKT4. The first type was the complete OKT4+ cell deficiency, the second was the normal percentage of OKT4+ cells with half immunofluorescence intensity and the third was the normal staining pattern with OKT4. Phytohaemagglutinin (PHA) and pokeweed mitogen (PWM) induced blastogenesis; PWM induced IgG synthesis, autologous and allogeneic mixed lymphocyte reaction, and Interleukin-2 (IL-2) production of their PBL were also normal. These results suggest that (i) the expression of determinant to OKT4 is transmitted as autosomal incomplete dominant trait and (ii) OKT4+ cell deficiency is not accompanied by a lack of the inducer/helper subset of T cells.